ANALISIS PERBANDINGAN PERHITUNGAN PAJAK PENGHASILAN BADAN TERUTANG MENGGUNAKAN UNDANG – UNDANG NO. 36 TAHUN 2008 TENTANG PPh DAN PERATURAN PEMERINTAH NO. 23 TAHUN 2018 TENTANG TARIF PPh FINAL (Studi Kasus : PRIMKOPPOL Resor Ciamis) - Mulyadi, Nanda Pramayasti; Dandan Irawan; Hasyim, M. Ardi Nupi (Program Studi Akuntansi IKOPIN, 2021)
Taxpayers often make mistakes in determining the tax burden payable which causeslosses for both the taxpayer and the government. The purpose of this study is todetermine the appropriate and beneficial tax provisions for cooperative businessentities in determining the income tax payable. The data obtained is sourced from theCooperative PHU Report for the 2020 Fiscal Year. The method of analysis carriedout is a comparative description analysis between the calculation of corporateincome tax using Law no. 36 of 2008 and Government Regulation no. 23 of 2018. Theresults of the study conclude that cooperatives are more profitable by usingGovernment Regulation no. 23 of 2018, because the tax burden borne by taxpayersis smaller than the calculation according to Law No. 36 of 2008, with the results ofthe discussion and analysis that the Ciamis Resort PRIMKOPPOL Cooperative hasa gross turnover of less than Rp4.8 billion in one financial year. And has fulfilled therequirements according to Government Regulation no. 23 of 2018.